Identification of Sitogluside as a Potential Skin-Pigmentation-Reducing Agent through Network Pharmacology. (23rd September 2021) - Guo, Haoran; Zeng, Hongliang; Fu, Chuhan; Huang, Jinhua; Lu, Jianyun; Hu, Yibo; Zhou, Ying; Luo, Liping; Zhang, Yushan; Zhang, Lan; Chen, Jing; Zeng, Qinghai
Abstract : Many traditional Chinese medicines (TCMs) with skin-whitening properties have been recorded in the Ben-Cao-Gang-Mu and in folk prescriptions, and some literature confirms that their extracts do have the potential to inhibit pigmentation. However, no systematic studies have identified the specific regulatory mechanisms of the potential active ingredients. The aim of this study was to screen the ingredients in TCMs that inhibit skin pigmentation through a network pharmacology system and to explore underlying mechanisms. We identified 148 potential active ingredients from 14 TCMs, and based on the average "degree" of the topological parameters, the top five TCMs ( Fructus Ligustri Lucidi, Hedysarum multijugum Maxim., Ampelopsis japonica, Pseudobulbus Cremastrae Seu Pleiones, and Paeoniae Radix Alba ) that were most likely to cause skin-whitening through anti-inflammatory processes were selected. Sitogluside, the most common ingredient in the top five TCMs, inhibits melanogenesis in human melanoma cells (MNT1) and murine melanoma cells (B16F0) and decreases skin pigmentation in zebrafish. Furthermore, mechanistic research revealed that sitogluside is capable of downregulating tyrosinase (TYR) expression by inhibiting the ERK and p38 pathways and inhibiting TYR activity. These results demonstrate that network pharmacology is an effective tool for the discovery of natural compounds with skin-whitening properties and determination of their possible mechanisms. Sitogluside is a novel skin-whitening active ingredient with dual regulatory effects that inhibit TYR expression and activity.